Comparison of Intravenous Ibuprofen with Paracetamol for Post Operative Pain Management after Laparoscopic Cholecystectomy - Naeem, Sobia; Wadud, Roheena; Laiq, Nasreen (Indus Journal of Bioscience Research, 2025)
Background: Pain following laparoscopic cholecystectomy remains a frequent problem, although the procedure is considered minimally invasive. Pain experienced during the postoperative period is attributed to handling of tissues, pneumoperitoneum, irritation of the diaphragm, which may result in prolonged hospitalization, although early mobilization is fundamental for accelerated recovery. Objective: To compare mean post-operative pain scores between intravenous ibuprofen and paracetamol after laparoscopic cholecystectomy. Study Design: Randomized controlled trial. Duration and Place of Study: This study was conducted from June 2024 to December 2024 in the Department of Anesthesia, Lady Reading Hospital, Peshawar. Methodology: A total of 68 patients aged 20 to 60 years undergoing laparoscopic cholecystectomy were included. Patients were randomly divided into two equal groups. One group received intravenous ibuprofen 800 milligrams, while the other group received intravenous paracetamol 1000 milligrams. Pain was assessed at the twelfth postoperative hour using visual analog scale. Mean pain scores of both groups were compared using independent sample t test. A p value ≤ 0.05 was taken as statistically significant. Results: The mean age was 39.50 ± 7.77 years in the ibuprofen group and 40.94 ± 8.00 years in the paracetamol group. The mean pain score at twelve hours was 1.50 ± 0.13 in the intravenous ibuprofen group and 2.09 ± 0.18 in the intravenous paracetamol group. Conclusion: Intravenous ibuprofen provides better postoperative pain relief compared to intravenous paracetamol after laparoscopic cholecystectomy.